Efficiency versus Insurance: Capital Income Taxation and Privatizing Social Security - Krzysztof Makarski; Joanna Tyrowicz; Oliwia Komada (Institute of Labor Economics (IZA), 2021)
We study the interactions between capital income tax and social security privatization in the context of rising longevity. In an economy with idiosyncratic income shocks, redistributive defined benefit social security provides some insurance against income uncertainty. This insurance comes at the expense of efficiency loss due to labor supply distortions. The existing view in the literature states that reducing this distortion by introducing (partially funded) defined contribution social security would reduce welfare because the loss of insurance and the transitory fiscal gap dominate the efficiency gains. However, prior research financed the transitory costs of the reform by taxing consumption. We show that in the context of longevity, capital income taxation provides a superior alternative: welfare gains are sufficient to outweigh the loss of insurance and transitory fiscal gap. We provide explanations for a mechanism behind this result and we reconcile our results with the earlier literature.
Keywords: C68; D72; E62; H55; J26; 330; longevity; capital income taxation; social security reform; fiscal policy; welfare effects